Pan-AKT Inhibitor Capivasertib With Docetaxel and Prednisolone in Metastatic Castration-Resistant Prostate Cancer: A Randomized, Placebo-Controlled Phase II Trial (ProCAID). Issue 3 (20th January 2021) - Crabb, Simon J.; Griffiths, Gareth; Marwood, Ellice; Dunkley, Denise; Downs, Nichola; Martin, Karen; Light, Michelle; Northey, Josh; Wilding, Sam; Whitehead, Amy; Shaw, Emily; Birtle, Alison J.; et al.
Abstract : PURPOSE: Capivasertib is a pan-AKT inhibitor. Preclinical data indicate activity in metastatic castration-resistant prostate cancer (mCRPC) and synergism with docetaxel. PATIENTS AND METHODS: ProCAID was a placebo controlled randomized phase II trial in mCRPC. Patients received up to ten 21-day cycles of docetaxel (75 mg/m 2 intravenous, day 1) and prednisolone (5 mg twice daily, oral, day 1-21) and were randomly assigned (1:1) to oral capivasertib (320 mg twice daily, 4 days on/3 days off, from day 2 each cycle), or placebo, until disease progression. Treatment allocation used minimization factors: bone metastases; visceral metastases; investigational site; and prior abiraterone or enzalutamide. The primary objective, by intention to treat, determined if the addition of capivasertib prolonged a composite progression-free survival (cPFS) end point that included prostate-specific antigen progression events. cPFS and overall survival (OS) were also assessed by composite biomarker subgroup for PI3K/AKT/PTEN pathway activation status. RESULTS: One hundred and fifty patients were enrolled. Median cPFS was 7.03 (95% CI, 6.28 to 8.25) and 6.70 months (95% CI, 5.52 to 7.36) with capivasertib and placebo respectively (hazard ratio [HR], 0.92; 80% CI, 0.73 to 1.16; one-sided P = .32). Median OS was 31.15 (95% CI, 20.07 to not reached) and 20.27 months (95% CI, 17.51 to 24.18), respectively (HR, 0.54; 95% CI, 0.34 to 0.88; two-sided P = .01). cPFS and OS results were consistent irrespective of PI3K/AKT/PTEN pathway activation status. Grade III-IV adverse events were equivalent between arms (62.2%). The most common adverse events of any grade deemed related to capivasertib were diarrhea, fatigue, nausea, and rash. CONCLUSION: The addition of capivasertib to chemotherapy did not extend cPFS in mCRPC irrespective of PI3K/AKT/PTEN pathway activation status. The observed OS result (a secondary end point) will require prospective validation in future studies to address potential for bias.